Structural health monitoring of tunnel liners - Sett, Han Htoo (Nanyang Technological University, 2022)
SFRC is a composite material that has high cracking resistance. Thus, it is used in precast tunnel segment production to resist stress induced by mechanical handling of tunnel boring machines. However, due to lack of experimental data and special design code makes unable to take full advantages of SFRC material properties. The aim is to study stress-strain behaviour of 3 points bending action using finite element method. The results showed SFRC can assist rebars in resisting tensile stress before cracking as well as increase cracking load. Therefore, it can be said that steel fibres can partially replace rebars. On the other hand, after cracking, rebars took majority of tensile stress. Thus, rebars are more effective after cracking as well as ultimate loads compared to steel fibres. For these reasons, special design rules should be made to take advantages of its properties yet still with considerations for its disadvantages. Finally, due to complexity and arbitrary nature of finite element method, experiments should be conducted to validate FEM results.